Faktor Premenstrual Syndrome pada Wanita Usia Subur 18 – 40 Tahun - Senja Himaya; Lilik Herawati; Ashon Sa’adi (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Premenstrual syndrome (PMS) is a collection of symptoms in reproductive women that appear on the 7-14 days before menstruation, such as physical, psychological, and behavioral disorders. Symptoms that often occur include excessive anxiety, irritability, breast pain, increased or decreased appetite, nausea, vomiting, acne, lumbago and back pain which can reduce productivity. Some experts say that PMS occur due to decreased serotonin levels caused by low physical activity, less or excess BMI, and hypertension. This research aims to analyze the relationship between PMS with physical activity, BMI, and hypertension in women 18-40 years old. This research was an observational analytic study with a cross sectional approach. The total sample was 54 reproductive women in Tuban District according to the inclusion criteria and using purposive sampling. Chi square statistical test was used to determine the significant level of data obtained level of significant α=0,05. After the chi square test was carried out, it was obtained physical activity with ρ = 0,012, BMI with ρ = 0,002, and hypertension with ρ = 0,003. This means there are relationship between physical activity, BMI, and hypertension with PMS. The conclusion is habits in proper and routine physical activity, normal BMI, and no history of hypertension can reduce the PMS complaints.